'Engagement' Discourses and the Student Voice: Connectedness, Questioning and Inclusion in Post-Covid Digital Practices. Issue 1 (8th September 2021) - Gourlay, Lesley; Campbell, Kristyna; Clark, Lauren; Crisan, Cosette; Katsapi, Evi; Riding, Katherine; Warwick, Ian
The Covid-19 crisis has led to a rapid pivot to online teaching and student engagement across higher education internationally, due to public health 'lockdown' measures. In March 2020 in the UK this move was sudden, and universities were forced to move their provision to digital formats with little preparatory time, and in many cases, inadequate training and experience. In the subsequent period, higher education institutions have prioritised the enhancement of digital education, with a range of strategic initiatives and training programmes for teaching staff. This paper, written by a staff-student partnership of authors, reports on two institutionally-supported studies conducted at a large, research-focused university in England, in which student views were sought on their experiences and priorities surrounding online engagement during the Covid-19 crisis. In our discussion of the findings, we argue that the student accounts challenge some of the mainstream assumptions about constructs such as student 'inclusivity', academic 'community' online, and teaching which encourages 'questioning', requiring us to think more deeply about what constitutes a meaningful and rich online educative experience. In the spirit of 'lessons learned' from the Covid-19 pandemic, the paper proposes alternative conceptions of these values, emphasising relationality, communities, difference, and the importance of an ethos of care. We conclude with a discussion of findings, implications for theory, research, policy and practice in a post-pandemic context, proposing that an ethos of care be recognised as central to the development of digital education and the practices and ethics of student engagement.